2021
DOI: 10.3389/fbioe.2021.606795
|View full text |Cite
|
Sign up to set email alerts
|

Successful Enzyme Colocalization Strategies in Yeast for Increased Synthesis of Non-native Products

Abstract: Yeast cell factories, particularly Saccharomyces cerevisiae, have proven valuable for the synthesis of non-native compounds, ranging from commodity chemicals to complex natural products. One significant challenge has been ensuring sufficient carbon flux to the desired product. Traditionally, this has been addressed by strategies involving “pushing” and “pulling” the carbon flux toward the products by overexpression while “blocking” competing pathways via downregulation or gene deletion. Colocalization of enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 75 publications
0
17
0
Order By: Relevance
“…The observed enhancements from spatially organised enzymes have been hypothesised to originate from either (i) the probabilistic diffusion of the intermediate metabolite towards the second enzyme (rather than into competing pathways), or (ii) the direct transfer of the intermediate metabolite between enzymes without diffusion into the bulk solution 1,[9][10][11][12][13] . Specifically for translationally fused enzymes, the former explanation is favoured in the literature 14,15 ; this is supported by a study on an FPPS and patchoulol synthase fusion that found constructs designed with short linker peptides slightly outperforming constructs with long linker peptides 4 . Another study investigating the fusion of geranyl diphosphate synthase (GPPS) with pinene synthase also found a small decrease in pinene titre as the linker length increases 16 .…”
Section: Introductionmentioning
confidence: 93%
“…The observed enhancements from spatially organised enzymes have been hypothesised to originate from either (i) the probabilistic diffusion of the intermediate metabolite towards the second enzyme (rather than into competing pathways), or (ii) the direct transfer of the intermediate metabolite between enzymes without diffusion into the bulk solution 1,[9][10][11][12][13] . Specifically for translationally fused enzymes, the former explanation is favoured in the literature 14,15 ; this is supported by a study on an FPPS and patchoulol synthase fusion that found constructs designed with short linker peptides slightly outperforming constructs with long linker peptides 4 . Another study investigating the fusion of geranyl diphosphate synthase (GPPS) with pinene synthase also found a small decrease in pinene titre as the linker length increases 16 .…”
Section: Introductionmentioning
confidence: 93%
“…Enzyme colocalization strategies increase the local concentration of substrates and minimize the efflux of intermediate metabolites by improving the binding efficiency of substrates to enzymes, which is an effective strategy to promote the conversion of different pyrophosphate precursors into diverse terpenes in S. cerevisiae and Y. lipolytica . , For example, in order to further improve the utilization of FPP after increasing the copy number of ERG20, Hu et al fused ERG20 with sesquiterpene synthase to shorten the distance between the enzyme and substrate in space . The results showed that after controlling for a single variable, the forward fusion enzyme containing the flexible linker GSG significantly increased the production of germacrene A in S. cerevisiae to 190.7 mg/L, which was six times higher than without the connecting peptide .…”
Section: Enzyme Engineering For Terpene Biosynthesis In Yeastsmentioning
confidence: 99%
“…Reverse micelles, stabilized by amphiphilic molecules, can form the basis for distributing enzymes in apolar organic solvents [33–38] . In this approach, the enzymes can be directly encapsulated inside without the need of any functional group modification.…”
Section: Introductionmentioning
confidence: 99%